On a new, burrow-associated species of Salmoneus Holthuis, 1955 (Decapoda: Alpheidae) from the Indo-West Pacific - Anker, Arthur (Zootaxa, 2024)
A new alpheid shrimp, Salmoneus ngae sp. nov., is described based on two specimens collected on a near-shore, seagrass-rubble sandflat on the north-eastern coast of New Caledonia. The material from Lombok, Indonesia, previously reported as S. alpheophilus Anker & Marin, 2006, is reidentified as S. ngae sp. nov. The new species is a member of the informal S. gracilipes Miya, 1972 species group and appears to be a symbiont of spacious and complex burrows of the snapping shrimp Alpheus rapax Fabricius, 1798. Thus, S. ngae sp. nov. joins an ecological guild within the genus Salmoneus, which is composed of seven species associated with burrows of Alpheus spp. in various parts of the world and in different habitats.